2015
DOI: 10.1002/adma.201404479
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Tolerant Superoleophobicity on Alginate Gel Surfaces Inspired by Seaweed (Saccharina japonica)

Abstract: Seaweed (Saccharina japonica) is found to have excellent superoleophobicity in salt solutions, which results from its high content of polysaccharides. Inspired by this, coatings with salt‐tolerant underwater superoleophobicity and ultralow oil adhesion are successfully fabricated using calcium alginate. During immersion in artificial seawater for 30 days, the coatings effectively repel various types of oil, including crude oil and viscous silicon oil, demonstrating their great potential as a marine oil‐repelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 45 publications
1
124
0
1
Order By: Relevance
“…[ 51 ] In addition, as a kind of marine plants, seaweeds, which possess rich content of polysaccharides, show salt-tolerant underwater superoleophobicity, leading to their remarkable anti-biofouling capability. [ 53 ] Inspired by these interesting phenomena, a novel strategy based on underwater superoleophobicity has been developed and exhibited great potential for effi cient antibiofouling. [ 27,[54][55][56] For example, by grafting poly(N-isopropylacrylamide) (PNIPAAm) on silicon nanowire arrays (SiNW) via surface-initiated atom transfer radical polymerization (SI-ATRP), Chen et al reported a thermal-responsive nanostructured (SiNW-PNIPAAm) surface, showing underwater superoleophobic property ( Figure 3 a).…”
Section: Bioinspired Underwater Superoleophobic Surfacesmentioning
confidence: 99%
“…[ 51 ] In addition, as a kind of marine plants, seaweeds, which possess rich content of polysaccharides, show salt-tolerant underwater superoleophobicity, leading to their remarkable anti-biofouling capability. [ 53 ] Inspired by these interesting phenomena, a novel strategy based on underwater superoleophobicity has been developed and exhibited great potential for effi cient antibiofouling. [ 27,[54][55][56] For example, by grafting poly(N-isopropylacrylamide) (PNIPAAm) on silicon nanowire arrays (SiNW) via surface-initiated atom transfer radical polymerization (SI-ATRP), Chen et al reported a thermal-responsive nanostructured (SiNW-PNIPAAm) surface, showing underwater superoleophobic property ( Figure 3 a).…”
Section: Bioinspired Underwater Superoleophobic Surfacesmentioning
confidence: 99%
“…[11][12][13] Inspired by Lotus leaves, 14,15 Salvinia, 16 seaweed 17 and other species in nature, [18][19][20][21][22] a variety of man-made approaches have been pursued to mimic those surfaces to create artificial superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A layer of water-retaining gel, calcium alginate, was coated onto the mesh. Since the absorbed water in the hydrogel acts as an intermediate phase that repels oil, the mesh is rendered superoleophobic underwater38. Hydrophobic fibres silanized with OTS were used as the regulating fibres.…”
Section: Resultsmentioning
confidence: 99%
“…The superoleophobic polyester mesh was fabricated as described elsewhere38. The mesh was first dip coated in a poly(ethylenimine) solution (10%, w/v).…”
Section: Methodsmentioning
confidence: 99%